The relationship between knowledge and perceptions towards acceptance of the COVID-19 vaccine among health students at University of Muhammadiyah Malang - Sendi Lia Yunita; Mutiara Titani; Jannah, Annisa Miftahul (Universitas Muhammadiyah Malang, 2022)
Background: COVID-19 (coronavirus disease 2019) is a disease caused by SARS-CoV-2 that attacks the respiratory system. The government has made various prevention efforts, one of which is to create a COVID-19 vaccination program. Objective: to determine the level of knowledge, perceptions, and acceptance of the COVID-19 vaccine, as well as the relationship between the level of knowledge and perceptions towards acceptance of the COVID-19 vaccine among Health Students. Methods: This study is a quantitative study with a cross-sectional study design using online questionnaire. A sample size of 100 respondents was obtained. The relationship between respondent characteristics, knowledge, and perceptions of COVID-19 vaccine acceptance was tested using the Chi-Square and Logistic Regression statistical tests. Results: It was found that 97% of respondents had good knowledge, 61% of respondents had positive perceptions, and 50% of respondents had high acceptance of the COVID-19 vaccine. There is a relationship between respondent gender (p=0.028) and acceptance of the COVID-19 Vaccine. There is a relationship between perception (p=0.000) and acceptance of the COVID-19 vaccine. However, there is no relationship between knowledge (p=0.500) and acceptance of the COVID-19 vaccine. Conclusion: There is a relationship between perception and acceptance of the COVID-19 vaccine.